PENGOLAHAN LIMBAH ORGANIK RUMAH TANGGA UNTUK PRODUKSI BIO-OIL SEDERHANA - Shofwatunnida Septarini; Ziadatul Amni; Wajizatul Amnia (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2023)
The bio-oil obtained was synthesized from household waste, especially food waste, using the pyrolysis method. This bio-oil production aims to reduce the pile of household waste in the research location that has not been resolved optimally. Municipal solid waste, such as food waste, is referred to as raw materials. In this study, several stages were carried out, starting from the preparation stage in the form of a survei of the research location and a survei of the amount of waste heap in the research location. Furthermore, the obtained municipal solid waste is processed into bio-oil products using a simple pyrolysis method with temperature 250, 300, and 350 oC. In addition, the resulting bio-oil products are characterized to determine the amount and content of chemical compounds. The objective of this research to determine the effect of various temperature of bio-oil production. The pyrolysis temperature affects the yield of the resulting bio-oilproduct, and the higher the pyrolysis operating temperature, the morediverse the chemical characteristics of the bio-oil product. Characteristics of bio-oil contain methanol with a percentage of about 64.48%. It means bio-oil can used for biofuel.